2010
DOI: 10.1200/jco.2009.24.1315
|View full text |Cite
|
Sign up to set email alerts
|

Absolute Risk of Endometrial Carcinoma During 20-Year Follow-Up Among Women With Endometrial Hyperplasia

Abstract: PURPOSE The severity of endometrial hyperplasia (EH)-simple (SH), complex (CH), or atypical (AH)-influences clinical management, but valid estimates of absolute risk of clinical progression to carcinoma are lacking. Materials and METHODS We conducted a case-control study nested in a cohort of 7,947 women diagnosed with EH (1970-2002) at one prepaid health plan who remained at risk for at least 1 year. Patient cases (N = 138) were diagnosed with carcinoma, on average, 6 years later (range, 1 to 24 years). Patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
138
2
15

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(165 citation statements)
references
References 22 publications
(23 reference statements)
6
138
2
15
Order By: Relevance
“…The time course from a diagnosis of endometrial hyperplasia to carcinoma is not well known. A case control study reported that the average time to diagnosis of cancer was six years in women with all types of EH (Lacey et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The time course from a diagnosis of endometrial hyperplasia to carcinoma is not well known. A case control study reported that the average time to diagnosis of cancer was six years in women with all types of EH (Lacey et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with PMB and endometrial polyps usually undergo endometrial sampling and the removal of polyps because foci of atypical hyperplasia or carcinoma may be present at histopathology in a benign-seeming polyp, or endometrial polyps and carcinoma may coexist in the same patient (Dubinsky et al, 1995;Lacey et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…endometrial intraepithelial neoplasia [EIN]) shows many of the molecular genetic changes of invasive carcinoma, yet only the presence of atypia is associated with a definite increase in carcinoma risk (l " Table 3) [15]. The expected rate of carcinoma development within 10 years is about 30 % [16]. When considering the risk of progression to invasive carcinoma it should be taken into account that invasive carcinomas are found in up to 48% of hysterectomy samples in this setting [17,18].…”
Section: Treatment Of Precursor Lesionsmentioning
confidence: 99%
“…In addition, one study found that atypical hyperplasia was reclassified as invasive carcinoma on second pathological assessment in 29 % of cases [17]. In contrast, the development of invasive carcinoma was very seldom in cases of hyperplasia without atypia (< 5 %) [16]. The following treatment recommendations can be deduced: Hyperplasia without atypia can be treated conservatively.…”
Section: Treatment Of Precursor Lesionsmentioning
confidence: 99%
“…Recent studies have revealed that less than 5% of simple and complex non-atypical hyperplasia cases undergo malignant transformation in the long term (20 years), whereas this percentage increases to 30% when there is an atypical hyperplasia [5,6].…”
Section: Introductionmentioning
confidence: 99%